Effects of serine or threonine in the active site of typical 2-cys prx on hyperoxidation susceptibility and on chaperone activity - Tairum, Carlos A. [UNESP]; Santos, Melina Cardoso [UNESP]; Breyer, Carlos Alexandre [UNESP]; de Oliveira, Ana Laura Pires [UNESP]; Cabrera, Vitoria Isabela Montanhero [UNESP]; Toledo-Silva, Guilherme; Mori, Gustavo Maruyama [UNESP]; Toyama, Marcos Hikari [UNESP]; Netto, Luis Eduardo Soares; de Oliveira, Marcos Antonio [UNESP] (MDPI, 2021)
Typical 2-Cys peroxiredoxins (2-Cys Prx) are ubiquitous Cys-based peroxidases, which are stable as decamers in the reduced state, and may dissociate into dimers upon disulfide bond formation. A peroxidatic Cys (CP) takes part of a catalytic triad, together with a Thr/Ser and an Arg. Previously, we described that the presence of Ser (instead of Thr) in the active site stabilizes yeast 2-Cys Prx as decamers. Here, we compared the hyperoxidation susceptibilities of yeast 2-Cys Prx. Notably, 2-Cys Prx containing Ser (named here Ser-Prx) were more resistant to hyperoxidation than enzymes containing Thr (Thr-Prx). In silico analysis revealed that Thr-Prx are more frequent in all domains of life, while Ser-Prx are more abundant in bacteria. As yeast 2-Cys Prx, bacterial Ser-Prx are more stable as decamers than Thr-Prx. However, bacterial Ser-Prx were only slightly more resistant to hyperoxidation than Thr-Prx. Furthermore, in all cases, organic hydroperoxide inhibited more the peroxidase activities of 2-Cys Prx than hydrogen peroxide. Moreover, bacterial Ser-Prx displayed increased thermal resistance and chaperone activity, which may be related with its enhanced stability as decamers compared to Thr-Prx. Therefore, the single substitution of Thr by Ser in the catalytic triad results in profound biochemical and structural differences in 2-Cys Prx.
Keywords: 2-Cys Prx; Catalytic triad; Chaperone; Hyperoxidation; Oligomerization; Organic hydroperoxides